Factors influencing the holding of Ilia Slatin’s Symphonic Concerts in Kharkiv in the 1870s–1880s - Lichuan Zhang (Культура України)
The purpose of this article is to determine the specifics of the organization and conduct of symphonic concerts led by I. I. Slatin under the auspices of the Kharkiv branch of the Russian Musical Society (KhRMS) during the 1870s–1880s. The article identifies the main factors that influenced this process: the organizational and financial conditions under which the musical society operated, as well as the orchestral performance practices of that time in Kharkiv. It is argued that the limited personnel and financial resources led to the involvement of periodically active theater enterprise in the city’s symphonic concerts. Factors such as the improving financial position of KhRMS in the 1880s, the opening of wind instrument classes at the Kharkiv Music School in 1886, and the formation of a pool of orchestral musicians in the city helped solve the issues of forming a full-fledged symphonic orchestra, which by the early 1890s consisted of professional musicians from Kharkiv.